The geology and geochemistry of the north-western portion of the Usushwana Complex, South-Eastern Transvaal - Riganti, Angela (Rhodes University, Faculty of Science, Department of Geology, 1992)
The 2.9 Ga old Usushwana Complex in the Piet Retief-Amsterdam area (south-eastern Transvaal) represents an exposed segment of a layered intrusion. It has the form of a dyke-like body elongated in a northwesterly direction, and extends to an estimated depth of 3000 -5500 m. Lithologically, the Complex consists of a cumulate succession of mafic rocks capped by granitoids and has intruded along the contact between the basement and the supracrustal sequences of the Kaapvaal Craton. Differentiation of an already contaminated gabbroic magma resulted in an ordered stratigraphic sequence comprising progressively more evolved lithotypes, with at least two imperfect cyclic units developed over a stratigraphic thickness of about 700 metres (Hlelo River Section). Meso- to orthocumulate textured gabbros and quartz gabbros grade upwards into magnetite- and apatite-bearing quartz gabbros, interlayered with discontinuous magnetitite horizons. The gabbros in turn grade into hornblende-rich, granophyric granodiorites. The differentiation process is regarded as having been considerably enhanced by the assimilation of acidic material, derived by partial melting of the felsic country rocks at the roof of the magma chamber. Recrystallisation of these rocks gave rise to the microgranites that locally overlie the granodiorites. Mineralogical, textural and geochemical features indicate a relatively advanced fractionation stage, suggesting that the exposed sequence of the Usushwana Complex in the study area represents the upper portion of the intrusion. No significant mineralised occurrences were identified. However, on the basis of similarities between the Usushwana Complex and other mafic layered intrusions which host significant ore deposits, it is suggested that economic concentrations of base metal(Cu-Ni) sulphides, PGE and chromitites are likely to be developed at lower stratigraphic levels.
Keywords: Geology -- South Africa -- Transvaal; Geochemistry -- South Africa -- Transvaal